Sederingsrutinens påverkan på resultatet av höftledsröntgen - Hjorth, Tove (2008)
Hip dysplasia is a common, inherited malformation of the coxofemoral joint that eventually leads to osteoarthrosis. Several breeds of dogs are affected and the prevalence varies between different breeds. As part of the effort to reduce the prevalence of hip dysplasia and select dogs suitable for breeding, radiological screening is performed by at least 12 months of age. Before the radiological examination the dog has to be chemically restrained, sedated or anesthetized. The sedation protocol used differs between veterinary clinics.